STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP TRADISI DALAM PROSES ADAT PERNIKAHAN BATAK TOBA DI GEREJA RAJAWALI KECAMATAN TAMPAN PEKANBARU - Sinaga, Yousheva; Eddison, Ahmad; Hambali, Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was motivated by Batak Toba people in the church of “karismatik” who consider a marriage hold in the church is a legal marriage, it is no longer hold a ceremony. But, Batak Toba people consider a marriage is not perfect without a ceremony because it can lead to conflicts in the family. It motivated the writer to take a title “A Study on the People Perception of the Traditions in the Process of Batak Toba Traditional Marriage in the Church Rajawali Kecamatan Tampan Pekanbaru”. The formulation of the research was as follows: “How is the people perception of the traditions in the process of Batak Toba traditional marriage in the Church Rajawali Kecamatan Tampan Pekanbaru?”. The objective of the research was to know how the people perception of the traditions in the process of Batak Toba traditional marriage in the Church Rajawali Kecamatan Tampan Pekanbaru is. The population of the research was 572 KK and the sample was 43 people. The instrument to collect the data were questionnaires which consist of 16 questions and interviews which consist of 4 questions. The data was analyzed by Qualitative Descriptive through percentage. Based on the calculation of percentage by respondents, the answer “good” was obtained as 70,79% placed on rank 66,67%-100%. Thus, the hyphothesis which explains the people perception that was “good” of the traditions in the process of Batak Toba traditional marriage in the Church Rajawali Kecamatan Tampan Pekanbaru was accepted. Based on the research finding, it can be inferred that a study on the people perception of the traditions in the process of Batak Toba traditionalmarriage in the Church Rajawali Kecamatan Tampan Pekanbaru was good. Key word: Perception, Traditional marriage (custom).